2022
DOI: 10.1002/acr.24816
|View full text |Cite
|
Sign up to set email alerts
|

Biopsychosocial Rehabilitation for Inflammatory Arthritis and Osteoarthritis Patients: A Systematic Review and Meta‐Analysis of Randomized Trials

Abstract: To assess the benefits and harms associated with biopsychosocial rehabilitation in patients with inflammatory arthritis (IA) and osteoarthritis (OA). METHODS:We performed a systematic review and meta-analysis. Data were collected through electronic searches of Cochrane CENTRAL, Medline, Embase, PsycINFO, and CINAHL databases up to March 2019. Trials examining the effect of biopsychosocial rehabilitation in adults with IA and/or OA were considered eligible, excluding rehabilitation adjunct to surgery. The prima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 57 publications
0
3
0
Order By: Relevance
“…So, I am going around and around in a cycle looking for ways to improve my [mental and physical] health, but it is harder to [engage in] healthy [RA management] as you have less energy and less ability to stick [to your treatment] because you are focusing on the pain and sadness more. (white woman, [25][26][27][28][29][30][31][32][33][34] Mental and physical well-being practices Practising daily 'positive thinking' was used by participants to cope with their RA symptoms and prognosis, and helps them stay focused on managing their RA. They described using humour, practising positive selftalk, surrounding themselves with positive people and engaging in mindfulness.…”
Section: Life Experiences and Well-being Practicesmentioning
confidence: 99%
See 1 more Smart Citation
“…So, I am going around and around in a cycle looking for ways to improve my [mental and physical] health, but it is harder to [engage in] healthy [RA management] as you have less energy and less ability to stick [to your treatment] because you are focusing on the pain and sadness more. (white woman, [25][26][27][28][29][30][31][32][33][34] Mental and physical well-being practices Practising daily 'positive thinking' was used by participants to cope with their RA symptoms and prognosis, and helps them stay focused on managing their RA. They described using humour, practising positive selftalk, surrounding themselves with positive people and engaging in mindfulness.…”
Section: Life Experiences and Well-being Practicesmentioning
confidence: 99%
“…You can overcome the pain by feeling better about yourself and your life. (Black woman, [25][26][27][28][29][30][31][32][33][34] Several used complementary medicine and other pain relief alongside their prescribed RA medical treatment. Regular use of RA medication was perceived to 'have a traumatising effect on the body' and using non-medical treatments was explained as to allow participants to feel in control of their care.…”
Section: Life Experiences and Well-being Practicesmentioning
confidence: 99%
“… 5 In recent years, various studies have indicated positive effects of a conservative biopsychosocial oriented approach in OA treatment. 6 , 7 Despite the recommendation of this treatment in OA, effect sizes of conservative treatment remain only small or at best moderate. 7 A possible explanation for this relative lack of treatment success could be related to suboptimal patient selection.…”
mentioning
confidence: 99%
“… 11 , 12 Individualized interdisciplinary multimodal pain treatments (IMPT) have resulted in positive improvement of several patient-reported and clinician measured outcomes regarding pain, disability and psychological factors in patients experiencing different chronic primary musculoskeletal pain disorders, 13 but also for self-reported pain, health and clinically observed disability in OA patients specifically. 6 This sort of treatment usually targets different components of the biopsychosocial model that contribute to the maintenance of chronic pain and/ or disability, requires active participation of the patients, and is given by a team of different health professionals ( e.g . physiotherapist, psychologist, physiatrist, social worker, etc.)…”
mentioning
confidence: 99%
See 1 more Smart Citation